2014
DOI: 10.4314/jab.v75i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Action du fongicide naturel NECO contre la cercosporiose noire (<i>Mycosphaerella fijiensis</i> Morelet) chez le bananier plantain (AAB) en Côte d’Ivoire

Abstract: Weekly evaluation of some phytopathological descriptors (PJFT, PJFN, PJF3, EEM, IS) of BSD on field treated revealed lower levels of infection by the black Sigatoka. Values of the EEM (DSD) were significantly reduced after each treatment, youngest leave touched by the disease (PJFT)is remained higher than those of untreated field, level of youngest leave necrosed (PJFN) was higher than 6 and index of disease severity (IS) was cancelled at the 16th week of observation. Conclusion and application of findings: Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
2
11
0
1
Order By: Relevance
“…For the essential oil of Cymbopogon citratus, with the smallest MIC (3±1.41 μl.ml -1 ) obtained for S. aureus 1; in this study, is contrary [19,39]. In contrast, this study confirmed the antibacterial activity of Neco®.…”
Section: Mic Mbc Ratiosupporting
confidence: 71%
See 1 more Smart Citation
“…For the essential oil of Cymbopogon citratus, with the smallest MIC (3±1.41 μl.ml -1 ) obtained for S. aureus 1; in this study, is contrary [19,39]. In contrast, this study confirmed the antibacterial activity of Neco®.…”
Section: Mic Mbc Ratiosupporting
confidence: 71%
“…Indeed, the latter reported a MICs 500µl.ml -1 , respectively for bacterial germs Staphylococcus entermedius and Pseudomonas aeruginosa. About the biobactericide Neco®, the fungicidal activity is the most mentioned in the literature, according to Doumbouya et al,(2012);Kassi et al, (2014)…”
mentioning
confidence: 99%
“…Similar results were obtained in an in vivo study by Silué et al (2018) who showed that the use of NECO against Colletotrichum gloeosporioides, the agent responsible for cashew nut leaf disease at concentrations of 1000 ppm reduced the severity of the disease by more than 50%. Work by Kassi et al (2014) showed that NECO applications at 5mL/L reduced the impact of black banana cercosporiosis. The observed antibacterial activity of the Biopesticide NECO could be explained by the existence of active ingredients with very strong antibacterial properties that would act directly on the crop pathogens and on the propagation organs (Camara et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This property would be due to the action of phenolic compounds such as thymol which is the major component of the essential oil of Ocimum gratissimum from which NECO was formulated. Thymol is known to be toxic to microorganisms and is thought to target the cytoplasmic membrane and wall of these microorganisms (Kassi et al, 2014). Indeed, much work has highlighted the efficacy of phenolic compounds, particularly that of thymol which has a very broad spectrum of antimicrobial action (Ajouri et al, 2008;Bounatirou, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These different compounds could therefore be at the origin of its effectiveness. In addition, studies by Kassi et al (2014) showed that the NECO biopesticide had an antifungal effect on Deightoniella torulosa (SYD.) ELLIS, a banana leaf parasite.…”
Section: -2-discussionmentioning
confidence: 99%